Program Pelatihan Bahasa Indonesia Untuk Imigran Di Badan Pelaksan Apartemen Sederhana Graha Utama Puspa - Ach. Syarif Hidayatullah; Bayu Priambodo (CV. Aksara Global Akademia, 2023)
Refugees are one of the long-standing problems in this world. The issue of refugees also participates in the discussion which is in the spotlight for the international community, because the problem of refugees is related to issues of humanity, namely related to human rights (HAM). This community service program aims to make it easy for immigrants to communicate with other people. Some of the benefits obtained are; will make it easier to communicate, minimize the occurrence of conflicts, there will be no cultural discrimination. The targets in this community service activity are refugees from abroad who live in Bapel Aparna Graha Utama Puspa.